HOW GENERATIVE LEADERSHIP INFLUENCES ENVIRONMENTAL BEHAVIOR AT WORK: THE MEDIATING ROLE OF MAN-NATURE ORIENTATION - Akhtar Nawaz; Dr. Sajjad Afridi; Muhammad Waseem (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the influence of Generative Leadership (GL) on Extra-Role Behavior (ERB) for the environment within the tourism and hospitality sector, focusing on the mediating role of Man-Nature Orientation (MNO). The study proposes a model to understand how GL can drive ERB, which is crucial for achieving long-term sustainability. Utilizing a quantitative, cross-sectional design, data were collected from 250 executives, managers, and owners in the tourism and hospitality industry. Results indicate that GL positively impacts ERB for the environment and that MNO mediates this relationship. The study provides practical insights for managers seeking to foster environmentally responsible behaviors among employees and contributes to sustainability in the tourism sector.